Flood Hazard Mapping and Vulnerability Analysis of Bishnumati River, Nepal - Dangol, Susheel; Bormudoi, Arnob (Journal on Geoinformatics, Nepal, 2017)
Flood is one of the striking water induced disaster that hits most of the part of the world. In Nepal also it is one of the serious disasters which affect the human lives and huge amount of property. The increase of population and squatter settlements of landless people living at the bank of the river has tremendous pressure in encroachment of flood plain making them vulnerable to the flood damage. The study describes the technical approach of probable flood vulnerability and flood hazard analysis. Bishnumati catchment was taken as area of study. One dimension model of HEC-RAS with HEC-GeoRAS interface in co-ordination with ArcGIS was applied for the analysis. Analysis shows that the flood area increases with flood intensity. Higher flood depth increases and lower flood depth decreases with increase in intensity of flood. Inundation of huge area of urban land indicates that in future human lives are more prone to flood disaster. Thus, the study may help in future planning and management for future probable disaster. Nepalese Journal on Geoinformatics, Vol. 14, 2015, page: 20-24